Rhamnolipids production by Pseudomonas aeruginosa RW9 using palm oil mill effluent sludge oil as a carbon source - Mohd Asmadi, Nur Aina Natasha; Zee, Kar Mun; Baskaran, Shobanah Menon; Ariffin, Hidayah; Wasoh, Helmi; Maeda, Toshinari; Hassan, Mohd Ali; Zakaria, Mohd Rafein (Elsevier Ltd, 2024)
The production of biosurfactants has garnered considerable attention in recent years due to their unique properties, which include the ability to enhance oil solubility in water, reduce surface tension, and exhibit low environmental toxicity. In this study, we investigated the production of biosurfactants by Pseudomonas aeruginosa RW9, using a renewable and non-food competitive, palm oil mill effluent (POME) sludge oil as a carbon source. Various carbon and nitrogen sources were introduced into the mineral salt medium to optimize biosurfactant production. The results demonstrated that P. aeruginosa RW9 successfully generated 1.57 g/L of rhamnolipids (RLs) biosurfactant. Liquid chromatography-mass spectrometry (LC-MS) analysis confirmed the presence of mono-RLs and di-RLs congeners. Furthermore, the RLs produced from POME sludge oil exhibited a significant reduction in surface tension, reaching 28.55 mN/m, and demonstrated efficient emulsification of diesel, with an emulsion index of up to 56.6 %. This research underscores the promising potential of using POME sludge oil as a sustainable substrate for RLs production. This approach not only adds value to a vastly available resource but also contributes to the production of environmentally friendly biochemicals.